2016
DOI: 10.2174/1566524016666160607090953
|View full text |Cite
|
Sign up to set email alerts
|

Subpopulations of Bone Marrow Mesenchymal Stem Cells Exhibit Differential Effects in Delaying Retinal Degeneration

et al.

Abstract: Bone marrow mesenchymal stem cells (BMSCs) have a therapeutic role in retinal degeneration (RD). However, heterogeneity of BMSCs may be associated with differential therapeutic effects in RD. In order to confirm this hypothesis, two subsets of rat BMSCs, termed rBMSC1 and rBMSC2, were obtained, characterized and functionally evaluated in the treatment of RD of Royal College of Surgeons (RCS) rats. Both subpopulations expressed mesenchymal stem cells (MSC) markers CD29 and CD90, but were negative for hemacyte a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…Electroretinogram (ERG) Examination. After the cell transplantation, ERG b-wave amplitude was measured weekly up to 4 weeks posttransplantation, with AVES-2000 electrophysiological apparatus (Kanghuaruiming S&T, Chongqing, China) as described previously [13,14]. An intensity of 6.325e-2 cd * s/m was applied, which allowed the recording of the response of photoreceptors to light stimulation.…”
Section: Autologous Rasc Transplantationmentioning
confidence: 99%
See 2 more Smart Citations
“…Electroretinogram (ERG) Examination. After the cell transplantation, ERG b-wave amplitude was measured weekly up to 4 weeks posttransplantation, with AVES-2000 electrophysiological apparatus (Kanghuaruiming S&T, Chongqing, China) as described previously [13,14]. An intensity of 6.325e-2 cd * s/m was applied, which allowed the recording of the response of photoreceptors to light stimulation.…”
Section: Autologous Rasc Transplantationmentioning
confidence: 99%
“…In addition to ASCs, other kinds of mesenchymal stem cell-based therapies for RDD have also shown promising outcomes in animal RDD models [13][14][15], prompting scientists and doctors to conduct clinical trials. The outcomes of several clinical trials have shown that some patients who received intravitreal transplantation of human ASCs have dense vitreous hemorrhage in the eyes, retinal detachment with severe proliferative vitreoretinopathy (PVR), and secondary epiretinal membrane (ERM) formation [16,17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is heterogeneity in the differentiation potential of MSC [20, 21], and there is heterogeneity in the expression of cell surface markers such as STRO-1 and CD271, and STRO-1 and CD271 expressing MSC have been demonstrated to possess enhanced immunomodulatory capacity [22, 23]. The heterogeneity of MSC may impair their therapeutic efficacy and introduce variations between studies [24].…”
Section: Introductionmentioning
confidence: 99%
“…Other typical examples included CX3CL1-expressing MSCs [115] and NT-4-engineered MSCs [116]. To date, most studies have supported the neuroprotective effect of MSCs [117], while rare evidence of neuronal replacement has been reported by means of MSC transplantation. According to observations by researchers, the mechanism of photoreceptor survival promotion is that MSCs strictly regulate their self-renewal capacity through anti-apoptotic, anti-inflammatory, immunomodulatory and angiogenic effects, which are based on MSC secretion of cytokines [118], growth factors and proteins, such as vascular endothelial growth factor, stromal cell-derived factor 1-alpha [119] and progranulin [12].…”
Section: Introductionmentioning
confidence: 99%